Սահմանադրական շարժումը Կ. Պոլսի հայ համայնքում - Լուսինե Նուրբեկյան (ՀՀ ԳԱԱ հրատ.)
In the second half of the 19th century, in the Turkish society, within the context of social reforms, the formation of national bodies and provision of legal status became an urgent issue for the Western Armenians.
Keywords: Armenian Diaspora; Social history and conditions; Social problems; Social reform